Antifeminist opinion leaders on YouTube: analysis of discourse and its influence on the perception of violence among young Spanish audiences - Brandariz Portela, Tania; del Pino-Díaz, David; Ortega-Fernández, Eglée; Padilla-Castillo, Graciela (Frontiers in Human Dynamics, 2025)
The present study examines the role of anti-feminist discourse on YouTube within the context of the rise of the feminist movement and the anti-feminist response on social media. It explores how such discourse may influence young people's perceptions of gender-based violence. The main aim was to analyze anti-feminist content created by influential opinion leaders on YouTube over a 6-month period by identifying discursive frameworks, examining audience interactions, and evaluating potential impacts on perceptions of gender-based violence. A mixed research design combining quantitative and qualitative analyses was employed. Fanpage Karma and Audiense Insights tools were used to examine engagement metrics and audience characteristics for 500 posts from five influential Spanish YouTubers. Findings revealed that, while criticism of feminism remains central to this discourse, the narratives have become more complex, often intertwining with far-right ideologies. The trivialization of violence against women was observed, with a predominantly young audience (25–34 years old) being mostly exposed to such content. Anti-feminist discourse on YouTube represents a multifaceted phenomenon that perpetuates misogynistic attitudes and serves as a gateway to broader radical-right ideologies. The growing reach and influence of these channels underscore the urgent need to develop educational strategies to counter such narratives among young audiences.